UPAYA GURU MENINGKATKAN DISIPLIN ANAK USIA 5-6 TAHUN DI PAUD BUNDA PONTIANAK - Ranti, Elsa Novia; Fadillah, Fadillah; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research was to describe the teacher?s efforts to improve disciplin of aged 5-6 years at PAUD Bunda Pontianak. The method use isn this research is descriptive method with a qualitative research approach. Data subjects in this research are 2 teacher?s in PAUD Bunda Pontianak. The techniques used in this research were observation, interview, and documentation using data collection tools like is observation guidelines, interview guides, and documentation picture. The results of data analysis show that the teacher?s afforts to improve disciplin in children aged 5-6 years in the indicators of learning planning, learning implemantation, and assessment at PAUD Bunda Pontinak. PAUD Bunda Pontianak learning planning has not been effecetive, implementation of learning has not been effective not according to plan, and the teacher immediately maks an assesment to see the disciline of the children. Assessment in PAUD Bunda Pontianak uses daily assessment in form the RPPH, anecdotal records, and monthly assessment that are collected monthly.Keyword : Assessment, Discipin, Teacher Effort.